2020
DOI: 10.1136/bmjdrc-2019-001132
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of weight loss in a CDC-recognized digital diabetes prevention program

Abstract: IntroductionTo investigate the impact of the digital Livongo Diabetes Prevention Program (DPP) on weight at 12 months, understand participants’ self-monitoring behaviors associated with greater weight loss, and evaluate the impact of coaching interactions on more frequent self-monitoring behaviors.Research design and methodsA retrospective analysis was performed using data from 2037 participants enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…Longer intervention duration tempered this relationship, however, suggesting that self-monitoring may be less effective for weight loss over time either because engagement declines or because rates of weight loss slow despite similar degrees of engagement. This primary finding supports the conclusions from prior reviews that focused predominantly on paper-based selfmonitoring methods (26,27) and is also consistent with large-scale retrospective studies from industry platforms that used self-monitoring (85)(86)(87)(88)(89).…”
Section: Key Findingssupporting
confidence: 87%
“…Longer intervention duration tempered this relationship, however, suggesting that self-monitoring may be less effective for weight loss over time either because engagement declines or because rates of weight loss slow despite similar degrees of engagement. This primary finding supports the conclusions from prior reviews that focused predominantly on paper-based selfmonitoring methods (26,27) and is also consistent with large-scale retrospective studies from industry platforms that used self-monitoring (85)(86)(87)(88)(89).…”
Section: Key Findingssupporting
confidence: 87%
“…The current findings showing that the amount of PA is related to WL align with previous research which found that higher PA prior to engaging in an aerobic exercise intervention (41) and greater PA levels during a WL program were associated with greater WL (42,43). Research examining whether energy balance behaviors (i.e., movement and eating behaviors), early in the intervention, and the change in those behaviors during an intervention, are predictive of WL success following a WL program primarily focused on diet is lacking.…”
Section: Discussionsupporting
confidence: 89%
“…The small difference between methods along with the relatively high willingness ratings across all methods (≥6.0 points for food intake and ≥5.7 points for alcohol consumption) suggests that participants generally seem willing to use all four methods for study/research purposes, even if they rate one method to be relatively more burdensome and less preferred than another. This is encouraging as more frequent engagement with (digital) food logging methods in behavioral interventions has been reported to be associated with greater weight loss over 3 [25] and 12 [26] months. Nonetheless, the actual usage of self-report methods to assess food intake decreases over time, even when efforts are made to reduce burden by, for example, using photographic food records [27].…”
Section: Discussionmentioning
confidence: 80%
“…The following are available online at https://www.mdpi.com/article/10 .3390/nu13103340/s1, Supplementary Methods: Food Intake Assessment Preference Questionnaire, Alcohol Consumption Assessment Preference Questionnaire; Supplementary Figure S1: Percentage of participants who rated each method as their preferred method of food intake assessment in those <25 years (Panel A), [25][26][27][28][29][30][31][32][33][34]…”
Section: Supplementary Materialsmentioning
confidence: 99%